Identifying Factors and Techniques to Decrease the Positive Margin Rate in Partial Mastectomies: Have We Missed the Mark?. Issue 3 (7th February 2016) - Edwards, Sara B.; Leitman, I. Michael; Wengrofsky, Aaron J.; Giddins, Marley. J.; Harris, Emily; Mills, Christopher B.; Fukuhara, Shinichi; Cassaro, Sebastiano
Abstract: Breast conservation therapy (BCT) has a reported incidence of positive margins ranging widely in the literature from 20% to 70%. Efforts have been made to refine standards for partial mastectomy and to predict which patients are at highest risk for incomplete excision. Most have focused on histology and demographics. We sought to further define modifiable risk factors for positive margins and residual disease. A retrospective study was conducted of 567 consecutive partial mastectomies by 21 breast and general surgeons from 2009 to 2012. Four hundred fourteen cases of neoplasm were reviewed for localization, intraoperative assessment, excision technique, rates, and results of re‐excision/mastectomy. Histologic margins were positive in 23% of patients, 25% had margins 0.1–0.9 mm, and 7% had tumor within 1–1.9 mm. Residual tumor was identified at—in 61 cases: 38% (disease at margin), 21% (0.1–0.9 mm), and 14% (1–1.9 mm). Ductal carcinoma in situ (DCIS) was present in 85% of residual disease on re‐excision and correlated to higher rates of re‐excision (p = <0.001), residual disease, and subsequent mastectomy. The use of multiple needles to localize neoplasms was associated with 2–3 times the likelihood for positive margins than when a single needle was required. The removal of additional margins at initial surgery correlated with improved rates of complete excision when DCIS was present. Patients must have careful analysis of specimen margins at the time of surgery and may benefit from additional tissue excision or routine shaving of the cavity of resection. Surgeons should conduct careful patient selection for BCT, in the context of multifocal, and multicentric disease. Patients for whom tumor localization requires bracketing may be at higher risk for positive margins and residual disease and should be counseled accordingly.